Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.4049/jimmunol.178.11.7317
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Myocardial Ischemia/Reperfusion Injury in TLR4-Deficient Mice Is Mediated through a Phosphoinositide 3-Kinase-Dependent Mechanism

Abstract: TLRs play a critical role in the induction of innate and adaptive immunity. However, TLRs have also been reported to mediate the pathophysiology of organ damage following ischemia/reperfusion (I/R) injury. We have reported that TLR4−/− mice show decreased myocardial injury following I/R; however, the protective mechanisms have not been elucidated. We examined the role of the PI3K/Akt signaling pathway in TLR4−/− cardioprotection following I/R injury. TLR4−/− and age-matched wild-type (WT) mice were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
162
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(171 citation statements)
references
References 46 publications
(86 reference statements)
7
162
0
2
Order By: Relevance
“…Recent studies have shown that activation of the TLR4-mediated NFκB pathway plays a role in ischemia/reperfusion (I/R) injury. For example, we (Hua et al, 2007;Li et al, 2005) and others have reported that TLR4-mediated NFκB signaling contributes to myocardial ischemia/reperfusion injury and TLR4 deficiency protects the myocardium from ischemic injury. TLR4 is also involved in the pathogenesis of I/R injury in liver (Zhai et al, 2004), kidney (Kim et al, 2005) and lung tissues (Shimamoto et al, 2006), TLRs have been identified in the central nervous system (CNS) and are thought to play an important role in the brain's response to pathogens as well as toxic cell debris (Bottcher et al, 2003;Bsibsi et al, 2002;Maslinska et al, 2004) and inflammatory or autoimmune CNS diseases (Chakravarty and Herkenham, 2005;Kerfoot et al, 2004).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Recent studies have shown that activation of the TLR4-mediated NFκB pathway plays a role in ischemia/reperfusion (I/R) injury. For example, we (Hua et al, 2007;Li et al, 2005) and others have reported that TLR4-mediated NFκB signaling contributes to myocardial ischemia/reperfusion injury and TLR4 deficiency protects the myocardium from ischemic injury. TLR4 is also involved in the pathogenesis of I/R injury in liver (Zhai et al, 2004), kidney (Kim et al, 2005) and lung tissues (Shimamoto et al, 2006), TLRs have been identified in the central nervous system (CNS) and are thought to play an important role in the brain's response to pathogens as well as toxic cell debris (Bottcher et al, 2003;Bsibsi et al, 2002;Maslinska et al, 2004) and inflammatory or autoimmune CNS diseases (Chakravarty and Herkenham, 2005;Kerfoot et al, 2004).…”
Section: Introductionmentioning
confidence: 78%
“…Nuclear proteins were isolated from hippocampal samples as previously described (Hua et al, 2005;Hua et al, 2007). NFκB binding activity was examined by EMSA in a 15 μl binding reaction mixture containing 15 μg of nuclear proteins and 35 fmol [γ-32 P] labeled doublestranded NFκB consensus oligonucleotide.…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular proteins were prepared from ischemic cerebral hemispheres (Hua et al 2007b), electrophoresed with SDS-polyacrylamide gel and transferred onto Hybond ECL membranes (Amersham Pharmacia, Piscataway, NJ) (Hua et al 2007a;Hua et al 2005;Hua et al 2007b). The ECL membranes were incubated with the appropriate primary antibody followed by incubation with peroxidase-conjugated secondary antibodies (Cell Signaling Technology, Inc.).…”
Section: Western Blotsmentioning
confidence: 99%
“…Knockout mouse studies have proven useful for identifying specific roles for DAMP receptors in modulating cardiac remodelling after injury or stress (summarised in Table 1). Global knockout or deficiency of TLR2 [34][35][36][37][38][39], TLR3 [40,41] and TLR4 [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] generally confers improvement of cardiac function and less adverse remodelling after injury, although detrimental effects have also been reported in TLR2 knockout mice [57]. In contrast to the perceived detrimental roles of TLRs 2, 3 and 4 in post-MI remodelling, a recent study suggested that TLR5 may play a beneficial role in protecting the heart from ischaemia/reperfusion injury [58].…”
Section: Damp Receptors and Cardiac Remodellingmentioning
confidence: 99%